Prelinguistic intersubjective and socio-communicative skills in infants with neurodevelopmental disabilities aged 0–36 months: A new assessment and parent support tool - Strazzer, Sandra; Sacchi, Daniela; Rigamonti, Roberta; Miccoli, Annalisa; Bonino, Margherita; Giancola, Serena; Germiniasi, Chiara; Montirosso, Rosario (Frontiers in Rehabilitation Sciences, 2023)
Background Although children with neurodevelopmental disability (NDD) present with several deficits, they partially share developmental impairments in prelinguistic intersubjective and socio-communicative skills, which are not easily assessed by conventional tests during the first years of life. Aim The current paper presents a new procedure to assess the prelinguistic intersubjective and socio-communicative skills of NDD children aged 0–36 months. A specific observation form template, called the Observation of Prelinguistic Intersubjective and Socio-Communicative Skills (OPISCoS) form, has been designed to systematically detect infant skills during daily routines (e.g., mealtime, playtime, desk activities). The OPISCoS form helps speech therapists to provide parents support to better perceive and understand early communicative signals from their children, avoiding the risk of excessive or reduced social stimulation. Methods The OPISCoS form is composed of three sections, namely, “Pragmatics and Communication,” “Decoding,” and “Expression,” which are useful to delineate the communication abilities of children with NDD and are not tapped by traditional batteries. Vignettes from clinical practice illustrate and provide exemplifications for using the OPISCoS form with NDD infants and their parents. Results The OPISCoS form was reported for two children and showed potential in detecting disrupted communicative behaviors and planning specific early interventions. Further, we observed an improvement not only in children's communicative abilities improve but also in their interactions with parents. From a clinical point of view, the OPISCoS form (1) offers an observational perspective of prelinguistic intersubjective and socio-communicative skills in infants with NDD and (2) may be useful to practitioners to enhance parents’ sensitivity to their infants’ communicative behavior. Conclusion The OPISCoS form was developed in clinical practice and is based on a very preliminary description of a new observational procedure as integration for the assessment of NDD children. The OPISCoS form appears to be a useful tool for the clinical assessment of prelinguistic intersubjective and socio-communicative skills in NDD infants as well as for promoting the quality of early parenting.